Acute and long-term results of bipolar radiofrequency catheter ablation of refractory ventricular arrhythmias of deep intramural origin - Igarashi, Miyako; Nogami, Akihiko; Fukamizu, Seiji; Sekiguchi, Yukio; Nitta, Junichi; Sakamoto, Naka; Sakamoto, Yuichiro; Kurosaki, Kenji; Takahashi, Yoshihide; Kimata, Akira; Komatsu, Yuki; Machino, Takeshi; et al. (Heart rhythm, 2020)
Successful bipolar radiofrequency catheter ablation (RFCA) of refractory ventricular arrhythmias (VAs) has been reported. However, the efficacy, safety, and long-term outcomes of bipolar RFCA of VAs are not fully determined. The purpose of this study was to evaluate the effectiveness and safety of bipolar RFCA in treating refractory VAs during long-term follow-up. Eighteen patients who underwent bipolar RFCA for ventricular tachycardia (VT) at 7 institutions were retrospectively investigated. Underlying heart diseases included remote myocardial infarction (n = 3 [17%]) and nonischemic cardiomyopathy (n = 15 [83%]). Although unipolar RFCA was performed in all patients, either it failed to suppress VT or VT recurred. The interventricular septum, left ventricular free wall, and left ventricular summit were targeted for bipolar RFCA. Acute success (VT termination and/or noninducibility) was achieved with bipolar RFCA in 16 patients (89%). Complications during the procedure included complete atrioventricular block (n = 2) and coronary artery stenosis (n = 1). One patient underwent chemical ablation after bipolar RFCA failure. At 12-month follow-up, VT reoccurred in 8 patients (44%). However, in patients with recurrence, VT burden had decreased: only 4 patients underwent re-RFCA, and only 1 of the 4 required chemical ablation. In the remaining 4 patients, re-RFCA was not required, as VT was controlled by medication or an implantable cardioverter-defibrillator. Bipolar RFCA is useful for acute suppression of refractory VT. Although VT recurrence rates during long-term follow-up were relatively high, we observed a significant reduction in VT burden.